A Retrospective Study: Trend in the Incidence of Tuberculosis Among Children in the Pekalongan - Irnawati Irnawati; Benny Arief Sulisyanto; Deisy Sri Hardini; Kosasih Bai Asmita; Tukimin bin Sansuwito (Proceedings Series on Health & Medical Sciences, 2021)
Mycobacterium tuberculosis is the leading cause of death worldwide from a single bacterial pathogen. World Health Organization (WHO) estimates that annually, 1 million children have tuberculosis disease and many more harbor a latent form of infection. Evaluation of time trends is an integral part of a comprehensive analysis of tuberculosis among children data. Objective: This study aimed to assess trends in tuberculosis among children incidence in the period 2015-2021. Tuberculosis among data were collected from tuberculosis database of Pekalongan Health Department. Data were analyzed by using Microsoft Excel. In the period 2015-2019, the tuberculosis among children incidence significantly increased from 11 to 165 cases, then drop in the period 2019-2021 from 165 to 32 cases. The largest increase in trend in the analysed period was observed for 2019, which showed an increase of 165 cases. Knowledge of the current tuberculosis among children burden in the population and its time trends will help to prioritise targets and future resource allocation to tuberculosis among children control.